Effects of temperature and Nocardia crassostreae on the immune response of the Pacific oyster, Magallana gigas - George Mason; Christopher Dwane; Luke A. Holmes; Robert P. Ellis; Lucy M. Turner; Manuela Truebano (Fish & Shellfish Immunology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Understanding the resource potential of natural hydrogen on Earth: Scientific gaps, uncertainties and recommendations - Giuseppe Etiope; Geoffrey S. Ellis; Omid H. Ardakani; Christopher J. Boreham; Peter Klitzke; Antonio Martín-Monge; Humberto L.S. Reis; Alexis S. Templeton; Hyeong Soo Kim; Eric Gaucher; Olivier Sissmann (Earth-Science Reviews, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Microclimatic moisture and the climate change resilience of lichen epiphytes – an applied model for temperate rainforest - Christopher J. Ellis (Biological Conservation, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Assessing the impact of climate change on verticillium wilt and the implications for cotton production in Australia - Karen A. Kirkby; Jane M. Kelley; Bethany Ellis; James R. Lawson; Christopher Nunn; Rebecca O. Darbyshire; Joanna Pardoe (International Journal of Biometeorology, 2026)
Climate change poses significant challenges for agricultural production, potentially altering crop distribution, productivity, and the prevalence of plant diseases. This study focuses on the fungus Verticillium dahliae which causes disease in over 400 plant species, significantly impacting cotton in most major cotton producing countries. We investigate how climate suitability for V. dahliae could change in the future, using New South Wales (NSW), Australia, as a case study. Our research examines the interplay between factors affecting the prevalence of V. dahliae infection, including fungal strain, temperature and rainfall. Using a 1992multi-criteria analysis approach, we evaluated climate suitability for V. dahliae under both historical and projected mid-21st century future climate conditions. This method combines peer-reviewed evidence with expert knowledge to assess potential impacts. Our findings suggest that climate change is likely to alter the number of months that are suitable for V. dahliae growth and potentially shift the distribution of fungal strains across NSW. Our modelling shows that the more aggressive defoliating strain is likely to become more prevalent in northern NSW, and the less aggressive non-defoliating strain is likely to become less prevalent, particularly in northern NSW. Our study provides valuable insights for agricultural planning and adaptation strategies in the face of climate change.

Biofluorescence as a tool to resolve crypsis in two bonefish species, Albula goreensis and Albula vulpes , with comments on other external morphology - Mason A. Thurman; Steven M. Lombardo; Ellis R. Loew; Paul S. Wills; Christopher Robinson; Aaron J. Adams (Journal of Fish Biology, 2025)
Bonefish Albula spp. in the Western Atlantic have historically been morphometrically and phenotypically indiscernible. We used biofluorescence in two sympatric, cryptic bonefish species, Albula goreensis and Albula vulpes , to develop a rapid and inexpensive in situ survey for species identification that can be used by managers and recreational anglers. Under ultraviolet (379–387 nm) and royal blue (440–457 nm) lights, the two species expressed differing biofluorescence on the iris, axil of the pectoral fins, the vent and the axil of the pelvic fins. Green biofluorescent patterns were most easily discernible under royal blue light while viewing through a Tiffen Yellow #12 longpass filter, although the use of an ultraviolet light with no visual filter was the most cost‐effective. We recommend the adoption of biofluorescent field surveys for bonefish using ultraviolet light on the axil of the pectoral fins and the vent for managers and anglers to differentiate A. goreensis and A. vulpes in real time. The application of this survey will allow for both fisheries’ independent and dependent data to be appropriately attributed at the species level, allowing for more effective management of the economically important western Atlantic bonefish fishery.

Species nativeness as a cultural paradigm in conservation - Lily M. van Eeden; Jeff Vance Martin; Jonathan Fisk; Lisa Lehnen; Erle C. Ellis; Michael C. Gavin; Adam C. Landon; Lincoln R. Larson; Kirsten M. Leong; Wayne Linklater; Christopher K. Williams; Richard E.W. Berl (Biological Conservation, 2025)

Lichen hydration, moisture dynamics and climate change: A synthesis of established methods and potential new directions - Giulia Canali; Pilar Hurtado; Paolo Giordani; Christopher Ellis (Fungal Biology Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The trade-off between photosynthetic rate and thallus moisture-demand explains lichen habitat association with the temperate rainforest - Amaris Ormond; Christopher J. Ellis; Claudia Colesie (Oecologia, 2025)
Temperate rainforests are globally rare, covering less than 1% of the Earth’s surface, with 15% of their suitable climate space located in Europe. These ecosystems are uniquely defined by diverse cryptogamic species, particularly epiphytic lichens, which play crucial roles in forest biodiversity, trophic interactions, and biogeochemical processes. However, the ecophysiology of temperate rainforest lichens, with the potential to explain their regional to local distribution, their primary productivity, growth rates and biomass accumulation, remains under researched. This study asked whether the coexistence of morphologically different species within Scotland’s temperate rainforest is driven by adaptation and subsequent species-sorting into contrasting microclimatic moisture environments. We examined seven species, analysing their biogeographic distributions and physiological responses to controlled moisture and light gradients to understand their degree of association with the temperate rainforest habitat. Our results indicated that species with the strongest temperate rainforest association had higher thallus water requirements (OptWC, MinWC and MaxWC) to achieve maximal photosynthesis (MaxNP) and that these appeared mediated by morphological traits. We found that, when morphological traits relating to water capture and retention, including layers of rhizine and tomentum, are linked to physiological optima, they can begin to explain how species across a spectrum of morphologies are differentially adapted or acclimated and associated to different degrees with the temperate rainforest climate. These findings also underscore the significance of ecophysiological knowledge for predicting the impacts of climate change on temperate rainforest biodiversity, since species’ microhabitat responses will be pivotal in understanding broader ecological shifts.

Scalable mangrove rehabilitation: Roots of success for Rhizophora stylosa establishment - Rory Mulloy; Christopher M. Aiken; Gordon Dwane; Megan Ellis; Emma L. Jackson (Ecological Engineering, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Model Sensitivity Analysis for Coastal Morphodynamics: Investigating Sediment Parameters and Bed Composition in Delft3D - Robert L. Jenkins; Christopher G. Smith; Davina L. Passeri; Alisha M. Ellis (Journal of Marine Science and Engineering, 2024)
Numerical simulation of sediment transport and subsequent morphological evolution rely on accurate parameterizations of sediment characteristics. However, these data are often not available or are spatially and/or temporally limited. This study approaches the problem of limited sediment grain-size data with a series of simulations assessing model sensitivity to sediment parameters and initial bed composition configurations in Delft3D, leading to improved modeling practices. A previously validated Delft3D sediment transport and morphology model for Dauphin Island, Alabama, USA, is used as the benchmark case. A method for the generation of representative sediment grain sizes and their spatially varying distributions is presented via end-member analysis of in situ surficial sediment samples. Derived sediment classes and their spatial distributions are applied to two sensitivity case simulations with increasing bed composition complexity. First, multiple sediment classes are applied in a single fully mixed layer, regardless of sediment type. Second, multiple sediment classes are applied in a thin, fully mixed transport layer with underlayers containing only the non-cohesive sediment classes below. Simulations were carried out in a probabilistic, Delft3D MorMerge configuration to capture long-term morphology change for 10 years. We found there is sensitivity to the inclusion of additional sediment classes and sediment distribution made evident in bed level and morphology change. Inclusion of highly mobile fine sediments altered model results in each sensitivity case. The model was also found to be sensitive to initial bed composition in terms of bed level and morphology change, with notable differences between sensitivity cases on decadal timescales, indicating an armoring effect in the second sensitivity case, which used the transport and underlayer bed configuration. The results of this study offer guidance for numerical modelers concerned with sediment behavior in coastal and estuarine environments.

Heavy-metal associated breast cancer and colorectal cancer hot spots and their demographic and socioeconomic characteristics - Madeline M. Tomlinson; Felicia Pugh; Alexandra N. Nail; Johnnie D. Newton; Karen Udoh; Stephie Abraham; Sandy Kavalukas; Brian Guinn; Rulla M. Tamimi; Francine Laden; Hari S. Iyer; J. Christopher States; et al. (Cancer Causes & Control, 2024)
Purpose Cancer registries offer an avenue to identify cancer clusters across large populations and efficiently examine potential environmental harms affecting cancer. The role of known metal carcinogens (i.e., cadmium, arsenic, nickel, chromium(VI)) in breast and colorectal carcinogenesis is largely unknown. Historically marginalized communities are disproportionately exposed to metals, which could explain cancer disparities. We examined area-based metal exposures and odds of residing in breast and colorectal cancer hotspots utilizing state tumor registry data and described the characteristics of those living in heavy metal-associated cancer hotspots. Methods Breast and colorectal cancer hotspots were mapped across Kentucky, and area-based ambient metal exposure to cadmium, arsenic, nickel, and chromium(VI) were extracted from the 2014 National Air Toxics Assessment for Kentucky census tracts. Among colorectal cancer ( n = 56,598) and female breast cancer ( n = 77,637) diagnoses in Kentucky, we used logistic regression models to estimate Odds Ratios (ORs) and 95% Confidence Intervals to examine the association between ambient metal concentrations and odds of residing in cancer hotspots, independent of individual-level and neighborhood risk factors. Results Higher ambient metal exposures were associated with higher odds of residing in breast and colorectal cancer hotspots. Populations in breast and colorectal cancer hotspots were disproportionately Black and had markers of lower socioeconomic status. Furthermore, adjusting for age, race, tobacco and neighborhood factors did not significantly change cancer hotspot ORs for ambient metal exposures analyzed. Conclusion Ambient metal exposures contribute to higher cancer rates in certain geographic areas that are largely composed of marginalized populations. Individual-level assessments of metal exposures and cancer disparities are needed.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Identifying and Constraining Marsh-Type Transitions in Response to Increasing Erosion over the Past Century - Alisha M. Ellis; Christopher G. Smith; Kathryn E. L. Smith; Jessica A. Jacobs (Estuaries and Coasts, 2024)
Marsh environments, characterized by their flora and fauna, change laterally in response to shoreline erosion, water levels and inundation, and anthropogenic activities. The Grand Bay coastal system (USA) has undergone multiple large-scale geomorphic and hydrologic changes resulting in altered sediment supply, depositional patterns, and degraded barrier islands, leaving wetland salt marshes vulnerable to increased wave activity. Two shore-perpendicular transect sites, one along a low-activity shoreline and the other in a high activity area of the same bay-marsh complex, were sampled to investigate how the marshes within 50 m of the modern shoreline have responded to different levels of increased wave activity over the past century. Surface sediments graded finer and more organic with increased distance from the shoreline while cores generally exhibited a coarsening upwards grain-size trend; all cores contained multiple large sedimentological shifts. 210 Pb-based mass accumulation rates over the last two decades were greater than the long-term (centurial) average at each site with the fastest accumulation rates of 7.81 ± 1.58 and 7.79 ± 1.63 kg/m 2 /year at the sites nearest the shoreline. A shoreline change analysis of three time-slices (1848–2017, 1957–2017, 2016–2017) shows increased erosion at both sites since 1848 with modern rates of −0.95 and −0.88 m/year. Downcore sedimentology, mass accumulation rates, and shoreline change rates paired with foraminiferal biofacies and identification of local estuarine indicator species, Paratrochammina simplissima , aided in identifying paleo marsh types, their relative proximity to the shoreline, and sediment provenance. The high-energy marsh site transitioned from middle marsh to low marsh in the 1960s, and the low-energy marsh site transitioned later, at the end of the twentieth and early twenty-first century, due to its more protected location. Marsh type transition corresponds chronologically with the coarsening upwards grain-size trend observed and the degradation of Grand Batture Island; since its submergence, signatures of multiple storm event have been preserved downcore.

Estimation of ammonia deposition to forest ecosystems in Scotland and Sri Lanka using wind-controlled NH3 enhancement experiments - Ajinkya G. Deshpande; Matthew R. Jones; Netty van Dijk; Neil J. Mullinger; Duncan Harvey; Robert Nicoll; Galina Toteva; Gothamie Weerakoon; Sarath Nissanka; Buddhika Weerakoon; Maude Grenier; Agata Iwanicka; et al. (Atmospheric Environment, 2024)

Method of test for CO2-based demand control ventilation systems: Benchmarking the state-of-the-art and the undervalued potential of proportional-integral control - Theresa Pistochini; Matthew Ellis; Fredrick Meyers; Antonea Frasier; Christopher Cappa; Deborah Bennett (Energy and Buildings, 2023)

Age, Growth, and Functional Gonochorism with a Twist of Diandric Protogyny in Goliath Grouper from the Atlantic Coast of Florida - Debra J. Murie; Daryl C. Parkyn; Christopher C. Koenig; Felicia C. Coleman; Christopher R. Malinowski; Jessica A. Cusick; Robert D. Ellis (Fishes, 2023)
The lack of data on the age, growth, and reproduction of the Atlantic Goliath Grouper Epinephelus itajara off the coasts of Florida (USA) makes it difficult to estimate the extent of their population recovery following the 1990 fishery closure, as well as the potential effects of the recent (2023) opening of a fishery for juveniles. Goliath Grouper from the Atlantic coast of Florida were non-lethally sampled for size (total length, TL), age (via fin rays), and sex and reproductive stage (via gonad biopsies, milt/egg expression, gonopores) from May to October 2010–2016. Of 653 unique fish captured (not including 118 recaptures), 257 (39.4%) were females (122–228 cm TL; 5–20 years old), 264 (40.0%) were males (104–225 cm TL; 4–22 years old), 100 (15.3%) were unsexed (82–211 cm TL; 3–15 years old), and 32 (4.9%) were protogynous hermaphrodites (108–209 cm TL; 5–20 years old). Protogyny was conclusively determined in two fish recaptured and re-biopsied that had transitioned from female to male. However, an overlap in the age and size of males and females, a 1:1 sex ratio, and the presence of relatively small, young, mature males, in combination with an apparently low functional sex change rate, all indicated that the sexual pattern of Goliath Grouper was functionally gonochoristic with the potential for diandric protogyny. Females > 10 years old were larger-at-age than males, and Goliath Grouper from the Atlantic coast were larger-at-age than fish from the Gulf of Mexico. These differences in age, growth, and reproductive strategy—as well as the nascent fishery for juveniles—need to be monitored closely so that the current and future reproductive capacity of the population continues to ensure growth and sustainability.

Spawning Migrations of the Atlantic Goliath Grouper along the Florida Atlantic Coast - Robert D. Ellis; Christopher C. Koenig; James V. Locascio; Christopher R. Malinowski; Felicia C. Coleman (Fishes, 2023)
Atlantic goliath grouper (Epinephelus itajara), the largest reef fish in the Western Atlantic, exhibit high site fidelity to home reefs but also undertake annual migrations to distant spawning sites. Once relatively common throughout Florida and the Caribbean, the species; is now considered vulnerable (i.e., threatened with extinction) due to overfishing and loss of juvenile mangrove habitat. Goliath grouper in the southeastern US form annual spawning aggregations on high-relief reefs located offshore of both the Gulf and Atlantic coasts of Florida, US. To determine spawning site fidelity and describe migration patterns to aggregations, we implanted 50 adult goliath grouper with acoustic transmitter tags from 2010 to 2013. Fish were tagged at known spawning sites off the Florida Atlantic coast and tracked as they moved through the FACT Network array of acoustic receivers. From 2010 to 2020, we collected ~7 million detections from tagged goliath grouper at 153 sites along the southeastern US Atlantic coast. Results of this long-term tracking indicate that adult goliath grouper are relatively sedentary during non-spawning months (Nov to June) but move significantly more prior to, during, and immediately after spawning (July to Oct). Inter-annual spawning site fidelity was high: between 80–93% of tagged fish returned to the same spawning sites each year. Arrival timing at spawning sites coincided with the August new moon, with males arriving earlier than females. Some individuals migrated distances greater than 400-km per year, with observed migration rates of up to 44-km per day prior to spawning. Long-term tagging data are critical for understanding movement patterns and developing management strategies for this species of special conservation concern.

Lichens as spatially transferable bioindicators for monitoring nitrogen pollution - Jay Delves; Jason E.J. Lewis; Niaz Ali; Saeed A. Asad; Sudipto Chatterjee; Peter D. Crittenden; Matthew Jones; Aysha Kiran; Bishnu Prasad Pandey; David Reay; Subodh Sharma; Dendup Tshering; et al. (Environmental Pollution, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Trophic ontogeny of a generalist predator is conserved across space - Christopher D. Stallings; James A. Nelson; Ernst B. Peebles; Gregory Ellis; Ethan A. Goddard; Nathaniel K. Jue; Alejandra Mickle; Orian E. Tzadik; Christopher C. Koenig (Oecologia, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Heat exposure misclassification: Do current methods of classifying diurnal range in individually experienced temperatures and heat indices accurately reflect personal exposure? - Alisa L. Hass; Kathryn McCanless; Winton Cooper; Kelsey Ellis; Christopher Fuhrmann; Kristina W. Kintziger; Margaret Sugg; Jennifer Runkle (International Journal of Biometeorology, 2022)

The contribution of macroalgae‐associated fishes to small‐scale tropical reef fisheries - Shaun K. Wilson; Christopher J. Fulton; Nicholas A.J. Graham; Rene A. Abesamis; Charlotte Berkström; Darren J. Coker; Martial Depczynski; Richard D. Evans; Rebecca Fisher; Jordan Goetze; Andrew Hoey; Thomas H. Holmes; et al. (Fish and Fisheries, 2022)
Macroalgae‐dominated reefs are a prominent habitat in tropical seascapes that support a diversity of fishes, including fishery target species. To what extent, then, do macroalgal habitats contribute to small‐scale tropical reef fisheries? To address this question we: (1) Quantified the macroalgae‐associated fish component in catches from 133 small‐scale fisheries, (2) Compared life‐history traits relevant to fishing (e.g. growth, longevity) in macroalgal and coral‐associated fishes, (3) Examined how macroalgae‐associated species can influence catch diversity, trophic level and vulnerability and (4) Explored how tropical fisheries change with the expansion of macroalgal habitats using a case study of fishery‐independent data for Seychelles. Fish that utilised macroalgal habitats comprise 24% of the catch, but very few fished species relied entirely on macroalgal or coral habitats post‐settlement. Macroalgal and coral‐associated fishes had similar life‐history traits, although vulnerability to fishing declined with increasing contribution of macroalgae association to the catch, whilst mean trophic level and diversity peaked when macroalgal‐associated fish accounted for 20%–30% of catches. The Seychelles case study revealed similar total fish biomass on macroalgal and coral reefs, although the biomass of primary target species increased as macroalgae cover expanded. Our findings reinforce that multiple habitat types are needed to support tropical fishery stability and sustainability. Whilst coral habitats have been the focus of tropical fisheries management, we show the potential for macroalgae‐associated fish to support catch size and diversity in ways that reduce vulnerability to overfishing. This is pertinent to seascapes where repeated disturbances are facilitating the replacement of coral reef with macroalgal habitats.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Abundant and persistent sulfur‐oxidizing microbial populations are responsive to hypoxia in the Chesapeake Bay - Keith Arora‐Williams; Christopher Holder; Maeve Secor; Hugh Ellis; Meng Xia; Anand Gnanadesikan; Sarah P. Preheim (Environmental Microbiology, 2022)
Summary The number, size and severity of aquatic low‐oxygen dead zones are increasing worldwide. Microbial processes in low‐oxygen environments have important ecosystem‐level consequences, such as denitrification, greenhouse gas production and acidification. To identify key microbial processes occurring in low‐oxygen bottom waters of the Chesapeake Bay, we sequenced both 16S rRNA genes and shotgun metagenomic libraries to determine the identity, functional potential and spatiotemporal distribution of microbial populations in the water column. Unsupervised clustering algorithms grouped samples into three clusters using water chemistry or microbial communities, with extensive overlap of cluster composition between methods. Clusters were strongly differentiated by temperature, salinity and oxygen. Sulfur‐oxidizing microorganisms were found to be enriched in the low‐oxygen bottom water and predictive of hypoxic conditions. Metagenome‐assembled genomes demonstrate that some of these sulfur‐oxidizing populations are capable of partial denitrification and transcriptionally active in a prior study. These results suggest that microorganisms capable of oxidizing reduced sulfur compounds are a previously unidentified microbial indicator of low oxygen in the Chesapeake Bay and reveal ties between the sulfur, nitrogen and oxygen cycles that could be important to capture when predicting the ecosystem response to remediation efforts or climate change.

Trait‐based response of lichens to large‐scale patterns of climate and forest availability in Norway - Nathan H. Phinney; Christopher J. Ellis; Johan Asplund (Journal of Biogeography, 2022)
Aim Functional traits offer a window into how organisms are adapted, and might acclimate, to environmental pressures. Despite being important in ecosystem function, lichens are underrepresented in trait‐based research; understanding how lichen functional traits vary with climate and habitat availability will be useful in predicting how communities will respond to climate change, for example, in wetter and warmer boreal and arctic ecosystems. Here, we assess the influence of macroclimate and forest availability on the spatial distribution of lichen traits across Norway. Location Norwegian mainland. Taxon Lichens. Methods We used relative trait frequency (RTF) data from LIAS gtm, a database combining trait information from LIAS (A Global Information System for Lichenized and Non‐Lichenized Ascomycetes) and GBIF (Global Biodiversity Information Facility) species observations. The 20 traits included photobiont types, growth forms, cortical features and reproductive modes. Nonparametric multiplicative regression (NPMR) models were used to explore the relationships between the environmental predictors of precipitation, temperature and forest availability. Results All traits showed significant relationships with the three environmental predictors. Photobiont type and reproductive mode traits produced the strongest models and revealed ecologically meaningful biogeographical patterns. Trebouxioid species peaked in colder, drier upland regions, while trentepohlioid lichens displayed an affinity for wetter and warmer climates and had a western and southern distribution. Cyanolichens increased with increasing precipitation and were strongly coastal. Sorediate and isidiate lichens were positively related to temperature, the former also increasing with forest cover. The above responses were consistent with the physiological and habitat requirements of the associated lichens. The remaining traits had weaker responses. Main conclusions Discrete traits (i.e. photobiont type and reproductive mode) with relatively low ecological plasticity reflect clear functional environmental responses at the large scale. By contrast, growth form and thallus structural features—proxies for continuous variables—are too variable within each given category to show observable distribution patterns.

Decline in Atlantic wolffish Anarhichas lupus in the North Sea : Impacts of fishing pressure and climate change - Joanna K. Bluemel; Simon H. Fischer; David W. Kulka; Christopher P. Lynam; Jim R. Ellis (Journal of Fish Biology, 2022)
Anarhichas lupus is a boreo‐Arctic species with biological characteristics often associated with vulnerability to overexploitation. Although not commercially targeted in the North Sea, A. lupus is a bycatch species in mixed demersal fisheries. Here we provide an overview of the status of A. lupus in the North Sea, as observed from commercial landings and fishery‐independent trawl survey data. A. lupus was once common across much of the central and northern North Sea but, since the 1980s, have declined in abundance, demographic characteristics (reduced size) and geographical range, with the shallower and more southerly parts of its range most impacted. A. lupus is still relatively frequent in the northern North Sea, where fishing intensity, though decreasing, is high. Bycatch through fishing remains a potential threat and, considering the likely impacts of predicted climate change on cold‐water species, risks of further regional depletion and/or range contraction remain. Whether or not A. lupus is able to re‐establish viable populations in former habitat in UK coastal waters is unknown. Given the lack of data, the precautionary principle would suggest that manageable pressures be minimized where the species and its habitat are at risk of further impacts, and more regular assessments of population status be undertaken.

Life‐history trade‐offs and the genetic basis of fitness in Arabidopsis thaliana - Thomas James Ellis; Froukje M. Postma; Christopher G. Oakley; Jon Ågren (Molecular Ecology, 2021)
Resources allocated to survival cannot be used to increase fecundity, but the extent to which this trade‐off constrains adaptation depends on overall resource status. Adaptation to local environmental conditions may therefore entail the evolution of traits that increase the amount of resources available to individuals (their resource status or ‘condition’). We examined the relative contribution of trade‐offs and increased condition to adaptive evolution in a recombinant inbred line population of Arabidopsis thaliana planted at the native sites of the parental ecotypes in Italy and Sweden in 2 years. We estimated genetic correlations among fitness components based on genotypic means and explored their causes with QTL mapping. The local ecotype produced more seeds per fruit than did the non‐local ecotype, reflected in stronger adaptive differentiation than was previously shown based on survival and fruit number only. Genetic correlations between survival and overall fecundity, and between number of fruits and number of seeds per fruit, were positive, and there was little evidence of a trade‐off between seed size and number. Quantitative trait loci for these traits tended to map to the same regions of the genome and showed positive pleiotropic effects. The results indicate that adaptive differentiation between the two focal populations largely reflects the evolution of increased ability to acquire resources in the local environment, rather than shifts in the relative allocation to different life‐history traits. Differentiation both in phenology and in tolerance to cold is likely to contribute to the advantage of the local genotype at the two sites.

Microclimates hold the key to spatial forest planning under climate change: Cyanolichens in temperate rainforest - Christopher J. Ellis; Sally Eaton (Global Change Biology, 2021)
There is deepening interest in how microclimatic refugia can reduce species threat, if suitable climatic conditions are maintained locally, despite global climate change. Microclimates are a particularly important consideration in topographically heterogeneous landscapes, while in some habitats, such as forests and woodlands, microclimates are also extremely labile and affected by management practices that could consequently be used to offset climate change impact. This study explored a conservation priority guild—cyanolichen epiphytes in temperate rainforest—quantifying the niche response to macroclimate, and landscape or woodland stand structures that determine the microclimate. Based on epiphyte survey in a core region of European temperate rainforest (western Scotland), a ‘random forest’ machine‐learning model confirmed a strong cyanolichen response to summer dryness, as well as the effects of distance to running water, topographic heatload and tree species identity, which modify the local moisture regime and/or lichen growth rates. By quantifying this response to macroclimate, landscape and stand structures, it was possible to estimate an extent to which woodland may be expanded in the future, to offset a negative effect of increasing summer dryness projected through to the 2080s. Using current policy as a yardstick, sufficient woodland expansion could be delivered relatively quickly for median impacted sites, but with times to woodland delivery extending over 10, 20 and 25 years for sites at the 75th, 90th and 95th percentiles of cyanolichen decline. Furthermore, the extent of new woodland required, and delivery times, increase almost threefold on average, as new woodland becomes distributed over wider riparian zones. These contrasting implications emphasize an urgent need for afforestation that achieves targeted spatial planning responsive to microclimates as refugia.

Left Atrial Appendage Closure for Patients with Cerebral Amyloid Angiopathy and Atrial Fibrillation: the LAA-CAA Cohort - Matthew Schrag; Brian Mac Grory; Alex Nackenoff; James Eaton; Eva Mistry; Howard Kirshner; Shadi Yaghi; Christopher R. Ellis (Translational Stroke Research, 2021)

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes - Christopher J. Fulton; Charlotte Berkström; Shaun K. Wilson; Rene A. Abesamis; Michael Bradley; Carolina Åkerlund; Luke T. Barrett; Abner A. Bucol; Dinorah H. Chacin; Karen M. Chong‐Seng; Darren J. Coker; Martial Depczynski; et al. (Fish and Fisheries, 2020)
Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.

Subsidized or stressed? Shifts in freshwater benthic microbial metagenomics along a gradient of alkaline coal mine drainage - Raven L. Bier; Jennifer J. Wernegreen; Rytas J. Vilgalys; Joseph Christopher Ellis; Emily S. Bernhardt (Limnology and Oceanography, 2020)
Chemical pollution mixtures enter aquatic environments and interact with microorganisms in eclectic ways with disparate consequences for microbial ecosystem services. Can using a thermodynamic framework help to determine the net influence of a chemical mixture on the functional capacity of benthic microbial communities? We examined this question by comparing benthic stream microbial communities exposed to a gradient of neutral‐alkaline coalmine effluent. Using a combination of approaches (metagenomics, quantitative polymerase chain reaction [qPCR], and functional assays), we show that functional genes and pathways of microbial communities growing in mine effluent differed in composition, but not diversity. The majority of functional genes and pathways that changed decreased at sites exposed to mine effluent, resulting in lower abundances of nitrogenase and methanogen genes and fermentation pathways. However, selenate reductase gene abundance increased with water and sediment concentration of an ecologically important contaminant at mined sites: selenium. Denitrification genes nosZ and nirK differed between sites: metagenome‐based nosZ increased with dissolved nitrate concentration and qPCR‐based nirK had a hump‐shaped pattern across the mining gradient. Osmoprotectant gene abundance did not change. Extracellular enzyme assays and alkaline phosphatase gene relative abundance suggested that mined stream microbial communities may be constrained by phosphorus bioavailability. Subsidies and stressors related to changes in a set of functional genes and pathways, but differences were not consistently predictable using thermodynamic expectations. This suggests that pairing hypotheses for expected subsidies and stressors with post hoc explorations can yield valuable directions for future study of how microbial functional capacity responds to pollutant mixtures.

The epiphytic lichen biota of Caucasian virgin forests: a comparator for European conservation - Jan Vondrák; Genadii Urbanavichus; Zdeněk Palice; Jiří Malíček; Irina Urbanavichene; Jiří Kubásek; Christopher Ellis (Biodiversity and Conservation, 2019)

Immersive field experiences lead to higher-level learning and translational impacts on students - Christopher Felege; Rebecca Romsdahl; Joshua Hunter; Cheryl Hunter; Susan Ellis-Felege (Journal of Environmental Studies and Sciences, 2019)

Characterisation of the NRF2 transcriptional network and its response to chemical insult in primary human hepatocytes: implications for prediction of drug-induced liver injury - Ian M. Copple; Wouter den Hollander; Giulia Callegaro; Fiona E. Mutter; James L. Maggs; Amy L. Schofield; Lucille Rainbow; Yongxiang Fang; Jeffrey J. Sutherland; Ewa C. Ellis; Magnus Ingelman-Sundberg; Stephen W. Fenwick; et al. (Archives of Toxicology, 2019)

Long-Term Persistence and Fire Resilience of Oak Shrubfields in Dry Conifer Forests of Northern New Mexico - Christopher H. Guiterman; Ellis Q. Margolis; Craig D. Allen; Donald A. Falk; Thomas W. Swetnam (Ecosystems, 2018)

Quantifying the anthropocene loss of bioindicators for an early industrial region: an equitable baseline for biodiversity restoration - Christopher J. Ellis; Rebecca Yahr; Brian J. Coppins (Biodiversity and Conservation, 2018)

A pilot(less) study on the use of an unmanned aircraft system for studying polar bears (Ursus maritimus) - Andrew F. Barnas; Christopher J. Felege; Robert F. Rockwell; Susan N. Ellis-Felege (Polar Biology, 2018)

Stoichiometric distribution models: ecological stoichiometry at the landscape extent - Shawn J. Leroux; Eric Vander Wal; Yolanda F. Wiersma; Louis Charron; Jonathan D. Ebel; Nichola M. Ellis; Christopher Hart; Emilie Kissler; Paul W. Saunders; Lucie Moudrá; Amy L. Tanner; Semra Yalcin (Ecology Letters, 2017)
Human activities are altering the fundamental geography of biogeochemicals. Yet we lack an understanding of how the spatial patterns in organismal stoichiometry affect biogeochemical processes and the tools to predict the impacts of global changes on biogeochemical processes. In this contribution we develop stoichiometric distribution models (St DM s), which allow us to map spatial structure in resource elemental composition across a landscape and evaluate spatial responses of consumers. We parameterise St DM s for a consumer‐resource (moose‐white birch) system and demonstrate that we can develop predictive models of resource stoichiometry across a landscape and that such models could improve our predictions of consumer space use. With results from our study system application, we argue that explicit consideration of the spatial patterns in organismal elemental composition may uncover emergent individual, population, community and ecosystem properties that are not revealed at the local extents routinely used in ecological stoichiometry. We discuss perspectives for further developments and application of St DM s to advance three emerging frameworks for spatial ecosystem ecology in an era of global change; meta‐ecosystem theory, macroecological stoichiometry and remotely sensed biogeochemistry. Progress on these emerging frameworks will allow for the integration of ecological stoichiometry and individual space use and fitness.

Fossil Giraffidae (Mammalia, Artiodactyla) from Lee Adoyta, Ledi-Geraru, and Late Pliocene Dietary Evolution in Giraffids from the Lower Awash Valley, Ethiopia - John Rowan; Ellis M. Locke; Joshua R. Robinson; Christopher J. Campisano; Jonathan G. Wynn; Kaye E. Reed (Journal of Mammalian Evolution, 2017)

A Conceptualization of the Utility of Subjective Cognitive Decline in Clinical Trials of Preclinical Alzheimer’s Disease - Rachel F. Buckley; Victor L. Villemagne; Colin L. Masters; Kathryn A. Ellis; Christopher C. Rowe; Keith Johnson; Reisa Sperling; Rebecca Amariglio (Journal of Molecular Neuroscience, 2016)

Distribution of skates and sharks in the North Sea: 112 years of change - Camilla Sguotti; Christopher P. Lynam; Bernardo García‐Carreras; Jim R. Ellis; Georg H. Engelhard (Global Change Biology, 2016)
How have North Sea skate and shark assemblages changed since the early 20th century when bottom trawling became widespread, whilst their environment became increasingly impacted by fishing, climate change, habitat degradation and other anthropogenic pressures? This article examines long‐term changes in the distribution and occurrence of the elasmobranch assemblage of the southern North Sea, based on extensive historical time series (1902–2013) of fishery‐independent survey data. In general, larger species (thornback ray, tope, spurdog) exhibited long‐term declines, and the largest (common skate complex) became locally extirpated (as did angelshark). Smaller species increased (spotted and starry ray, lesser‐spotted dogfish) as did smooth‐hound, likely benefiting from greater resilience to fishing and/or climate change. This indicates a fundamental shift from historical dominance of larger, commercially valuable species to current prevalence of smaller, more productive species often of low commercial value. In recent years, however, some trends have reversed, with the (cold‐water associated) starry ray now declining and thornback ray increasing. This shift may be attributed to (i) fishing, including mechanised beam trawling introduced in the 1960s–1970s, and historical target fisheries for elasmobranchs; (ii) climate change, currently favouring warm‐water above cold‐water species; and (iii) habitat loss, including potential degradation of coastal and outer estuarine nursery habitats. The same anthropogenic pressures, here documented to have impacted North Sea elasmobranchs over the past century, are likewise impacting shelf seas worldwide and may increase in the future; therefore, parallel changes in elasmobranch communities in other regions are to be expected.

Meta-studies in land use science: Current coverage and prospects - Jasper van Vliet; Nicholas R. Magliocca; Bianka Büchner; Elizabeth Cook; José M. Rey Benayas; Erle C. Ellis; Andreas Heinimann; Eric Keys; Tien Ming Lee; Jianguo Liu; Ole Mertz; Patrick Meyfroidt; et al. (Ambio, 2016)

Phylogeography of six codistributed New Zealand cicadas and their relationship to multiple biogeographical boundaries suggest a re‐evaluation of the Taupo Line - Emily A. Ellis; David C. Marshall; Kathy B. R. Hill; Christopher L. Owen; Peter J. J. Kamp; Chris Simon (Journal of Biogeography, 2015)
Aim Comparative biogeographers question the extent to which codistributed species respond similarly to environmental change. Such responses should create similar, appropriately timed patterns of cladogenesis among codistributed taxa compared to evolutionary independence, which may limit the predictions that can be made for unstudied species. Here, we compare phylogeographical patterns across ecologically divergent, codistributed taxa in the light of New Zealand's palaeohistory. Location North Island, New Zealand. Methods Mitochondrial DNA from six codistributed cicada species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta , K. scutellaris and K. dugdalei ) was analysed using phylogenetic methods and molecular dating techniques. We analysed phylogeographical distributions using analysis of molecular variance ( AMOVA ) to determine the significance of hypothesized biogeographical boundaries for clade differentiation and spatial distribution of genetic diversity. Results Five species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta and K. scutellaris ) show various degrees of intraspecific concordance with biogeographical boundaries found in previously studied taxa – the Kauri Line, the Northland Line and the newly identified Cockayne's Line. Clade splits of forest species correlate with the Kauri Line and/or Northland Line, whereas splits of scrub/hill species correlate with Cockayne's Line. Four species ( Kikihia ochrina , K. cutora , K. laneorum and K. cauta ) diversified before the Last Glacial Maximum ( LGM , 20 ka), whereas two species ( K. scutellaris and K. dugdalei ) show only post‐ LGM diversification. Main conclusions Despite species idiosyncrasies, we see the imprint of shared palaeoclimatic/geological events. We distinguish between (1) the importance of biogeographical lines as the demarcation between older genetically diverse and newer genetically depauperate populations, and (2) the importance of lines as biogeographical boundaries between sister clades. We also stress the importance of dating clade splits to ensure consistency with explanations for the biogeographical lines in question. We suggest that the Taupo Line has been overemphasized as a biogeographical boundary, whereas the importance of the mountain axis running north‐east to south‐west (‘Cockayne's Line’) has been overlooked.

Archaeobotanical evidence for climate as a driver of ecological community change across the anthropocene boundary - Christopher J. Ellis; Rebecca Yahr; Rocío Belinchón; Brian J. Coppins (Global Change Biology, 2014)
The biodiversity response to climate change is a major focus in conservation research and policy. Predictive models that are used to project the impact of climate change scenarios – such as bioclimatic envelope models – are widely applied and have come under severe scrutiny. Criticisms of such models have focussed on at least two problems. First, there is an assumption that climate is the primary driver of observed species distributions (‘climatic equilibrium’), when other biogeographical controls are often reliably established. Second, a species' sensitivity to macroclimate may become less relevant when impacts are down‐scaled to a local level, incorporating a modifying effect of species interactions structuring communities. This article examines the role of different drivers (climate, pollution and landscape habitat structure) in explaining spatial community variation for a widely applied bioindicator group: lichen epiphytes. To provide an analysis free of ‘legacy effects’ (e.g. formerly higher pollution loads), the study focused on hazel stems as a relatively short‐lived and recently colonized substratum. For communities during the present day, climate is shown to interact with stem size/age as the most likely explanation of community composition, thus coupling a macroclimatic and community‐scale effect. The position of present‐day communities was projected into ordination space for eight sites in E ngland and compared to the position of historical epiphyte communities from the same sites, reconstructed using preserved hazel wattles dating mainly to the 16th Century. This comparison of community structure for the late‐ to post‐Mediaeval period, with the post‐Industrial period, demonstrated a consistent shift among independent sites towards warmer and drier conditions, concurrent with the end of the Little Ice Age. Long‐term temporal sensitivity of epiphyte communities to climate variation thus complements spatial community patterns. If more widely applied, preserved lichen epiphytes have potential to generate new baseline conditions of environment and biodiversity for preindustrial lowland E urope.

Implications of Ash Dieback for Associated Epiphytes - CHRISTOPHER J. ELLIS; BRIAN J. COPPINS; SALLY EATON; JANET SIMKIN (Conservation Biology, 2013)

Cattle MHC nomenclature: is it possible to assign sequences to discrete class I genes? - John A. Hammond; Steven G. E. Marsh; James Robinson; Christopher J. Davies; Michael J. Stear; Shirley A. Ellis (Immunogenetics, 2012)

Predicting the biodiversity response to climate change: challenges and advances - CHRISTOPHER J. ELLIS (Systematics and Biodiversity, 2011)

Epiphyte sensitivity to a cross-scale interaction between habitat quality and macroclimate: an opportunity for range-edge conservation - Vivyan Lisewski; Christopher J. Ellis (Biodiversity and Conservation, 2010)

Strategy to Prevent Drug-Related Hypersensitivity in Folate-Targeted Hapten Immunotherapy of Cancer - Yingjuan Lu; Patrick J. Klein; Elaine Westrick; Le-Cun Xu; Hari Krishna R. Santhapuram; Alicia Bloomfield; Stephen J. Howard; Iontcho R. Vlahov; P. Ron Ellis; Philip S. Low; Christopher P. Leamon (The AAPS Journal, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

Local extent of old‐growth woodland modifies epiphyte response to climate change - Christopher J. Ellis; Rebecca Yahr; Brian J. Coppins (Journal of Biogeography, 2009)
Aim To quantify the interaction between climate and woodland continuity in determining the bioclimatic response of lichen epiphytes. Location Northern Britain (Scotland). Methods Indicator‐species analysis was used to pre‐select lichen epiphytes along parallel gradients in climate and the extent of old‐growth woodland. Nonparametric multiplicative regression was used to describe in a predictive model the individualistic response of selected species, which were projected based on climate‐change scenarios and contrasting patterns of simulated woodland loss or gain. Species with a similar response were grouped using a novel application of cluster analysis to summarize the potentially huge number of projected outcomes. Projected patterns of occurrence under climate‐change scenarios were examined for different levels of old‐growth woodland extent. Results Forty‐two lichen species were statistically significant indicator species in oceanic woodlands, and old‐growth indicators under suboptimal climatic conditions. Responses to climate‐change scenarios were contrasting, with one group comprising species projected to increase in extent in response to climate warming, and other response groups projected to decrease in occurrence, possibly in response to shifting rainfall patterns. The occurrence of all response groups had a positive relationship with old‐growth woodland extent. Main conclusions An ‘oceanic’ biogeographical group of epiphytes identified using the baseline climatic and present‐day woodland setting comprised species with a cyanobacterial photobiont or tropical phytogeographical affinities. However, within this group the individual species responses to climate‐change scenarios were contrasting. Additionally, group responses may be poorly matched with simple ecological traits. However, the studied interaction between climate and habitat continuity suggests that the impact of climate change might be offset for certain lichen epiphytes by appropriate management of woodland resources, for example, expansion of native woodland around remnant old‐growth stands.

A brain-behaviour initiative for South Africa: the time is right - Dan J. Stein; Willie Daniels; Robin Emsley; Brian Harvey; Jonathan Blackburn; Paul Carey; George Ellis; Nicola Illing; Alan Flisher; Hanlie Moolman-Smook; Kelvin Mwaba; Rajkumar Ramesar; et al. (Metabolic Brain Disease, 2006)

Contrasting functional traits maintain lichen epiphyte diversity in response to climate and autogenic succession - Christopher J. Ellis; Brian J. Coppins (Journal of Biogeography, 2006)
Aim Lichen epiphytes are important for biodiversity conservation and are also widely applied as environmental indicators. However, biogeographical and ecological knowledge underpinning lichen epiphyte conservation, and the use of lichens as indicators, is based primarily on a limited range of ‘macrolichen’ species. Wider trends in epiphyte biodiversity remain largely unexplored. This paper examines the community structure of lichen epiphytes on aspen ( Populus tremula L.) in Scotland, including species across all functional groups and comprising, therefore, taxonomically difficult ‘microlichens’. Location Northern Britain (Scotland). Methods Epiphytes were sampled from 12 sites throughout Scotland and examined at two scales: between and within aspen stands. Species were classified into contrasting functional groups and ordination by detrended correspondence analysis was used to summarize community structure. Results Within aspen stands (between trees) epiphyte communities showed successional patterns related to tree age. These successional patterns changed predictably for stands aligned along a climatic gradient (between stands). Main conclusions A dual climatic–successional trend in epiphyte community structure is presented. Large‐scale trends in epiphyte diversity are explained as the local response of species with contrasting functional traits to climate and autogenic succession. Turnover of functional groups between stands is positively related to β ‐diversity, and ecological limits to the frequency of contrasting functional groups are presented. Accordingly, the study and application of lichen species with similar functional traits may inadequately represent patterns of biodiversity. This prompts criticism of the currently accepted conservation strategy, i.e. (1) an emphasis in the conservation literature on ‘macrolichen’ species with similar ecologies and (2) the application of lichen indices over climatically variable geographical areas.

ISAG/IUIS-VIC Comparative MHC Nomenclature Committee report, 2005 - Shirley A. Ellis; Ronald E. Bontrop; Doug F. Antczak; Keith Ballingall; Christopher J. Davies; Jim Kaufman; Lorna J. Kennedy; James Robinson; Douglas M. Smith; Michael J. Stear; Rene J. M. Stet; Matthew J. Waller; et al. (Immunogenetics, 2006)

In vivo videomicroscopy reveals differential effects of the vascular-targeting agent ZD6126 and the anti-angiogenic agent ZD6474 on vascular function in a liver metastasis model - Hemanth Varghese; Lisa Mackenzie; Alan Groom; Christopher Ellis; Anderson Ryan; Ian Macdonald; Ann Chambers (Angiogenesis, 2004)

Paleolimnology of Lake Tanganyika, East Africa, over the past 100 kyr - Christopher A. Scholz; John W. King; Geoffrey S. Ellis; Peter K. Swart; J. Curt Stager; Steven M. Colman (Journal of Paleolimnology, 2003)

The natural abundance of 15N in mat-forming lichens - Christopher J. Ellis; Peter D. Crittenden; Charles M. Scrimgeour; Carl Ashcroft (Oecologia, 2003)

A Transportation Model Assessment of the Risk to Native Mussel Communities from Zebra Mussel Spread - Daniel W. Schneider; Christopher D. Ellis; Kevin S. Cummings (Conservation Biology, 1998)

A Transportation Model Assessment of the Risk to Native Mussel Communities from Zebra Mussel Spread - Daniel W. Schneider; Christopher D. Ellis; Kevin S. Cummings (Conservation Biology, 1998)
When introduced species threaten native flora and fauna, protection requires an analysis of the risk that native species face from the spread of the introduced species. Models of invading species, however, often do not include a dynamic component of risk. North American freshwater mussels are at risk of fouling by the introduced zebra mussel ( Dreissena polymorpha ). Predictions of the risk to native mussel communities of invasion by the zebra mussel can help prioritize conservation efforts. We present a model for the spatial analysis of zebra mussel spread that allows the characterization of relative risk of infestation to the high‐quality mussel communities of Illinois streams. A gravity model, constrained at origin and destination, was parameterized with data on boat use at 120 boat landings in Illinois. The risk of spread of zebra mussels depends on the number of boat trips from infested waters, which in turn depends on distance from an infested water, boat use at a site, and the position of a lake within a river system. Habitats supporting a high diversity of native mussels and threatened and endangered species are at risk of infestation from reservoirs upstream. Invasion of inland lakes and reservoirs in Illinois is predicted to occur first at areas of high boat use close to currently infested waters, including the Fox Chain of Lakes, followed by central Illinois reservoirs. These reservoirs will act as stepping stones, facilitating the invasion of lakes upstream of critical native mussel habitats. Efforts to protect waters that center on prevention of the initial invasion of stepping‐stone lakes could significantly reduce the risk of infestation. Education and inspection efforts are predicted to be more effective than quarantine because quarantines would displace boat traffic to critical habitats. The class of models presented here is useful for predicting risk of invasion when complete data on vector movement are not available. Evaluación de Riesgo de un Modelo de Transportación para Comunidades Nativas de Mejillones Debido a la Dispersión del Mejillon Zebra Cuando las especies introducidas amenazan la flora y fauna nativa, la protecci ó n requiere de un análisis del riesgo que las especies nativas enfrentan debido a la disperción de las especies introducidas. Sin embargo, los modelos de invasi ó n de especies frecuentemente no incluyen un componente dinámico de riesgo. Los mejillones de Norteamérica se encuentran en riesgo de ser entampados por el mejill ó n zebra introducido ( Dreissena polymorpha ). Las predicciones de riesgo para las comunidades nativas de mejillones podrían ayudar a priorizar los efuerzos de conservación. Presentamos un modelo de análisis espacial de la dispersión del mejillón zebra que permite la caracterización del riesgo relativo de infestación de comunidades de mejillones de alta calidad de los arrollos de Illinois. Un modelo de gravedad, forzado en el origen y destino, se parametrizó con datos de uso de botes en 120 arribos en Illinois. El riesgo de dispersión del mejillón zebra depende del número de viajes de boes a zonas infestadas, que a su vez depende de la distancia a la que se encuentran las aguas infestadas, el uso del bote en el sitio y la posición del lago dentro del sistema riverino. Los hábitats que soportan una gran diversidad de mejillones nativos y de especies amenazadas o en peligro se encuentran en riesgo de infestación por los reservorios aguas arriba. Se predice que la invasión de lagos y reservorios tierra adentro en Illinois, ocurriría primero en áreas con un alto uso de botes, cercanas a las zonas actualmente infestadas incluyendo la cadena de Lagos Fox, seguido de los reservorios del centro de Illinois. Estos reservorios actuarían como trampolines, facilitando la invasión de lagos rio arriba, con hábitat crítico para especies de mejillones nativos. Los esfuerzos para proteger las aguas que se centren en la prevención de la invasión inicial de lagos‐trampolín podría reducier significativamente el riesgo de infestación. Se predice que la educación e inspección de esfuerzos serían mas efectivos que las cuarentenas, puesto que las cuarentenas podrían desplazar el tráfico de botes hacia hábitats críticos. La clase de modelos presentados en este trabajo son de gran uso para la predicción de riesgos de invasión cuando los datos de vector de movimiento no se encuentran a la mano.

An automated method for analysis and visualization of laser doppler velocimetry data - Timothy M. Healy; Jeffrey T. Ellis; Arnold A. Fontaine; Christopher A. Jarrett; Ajit P. Yoganathan (Annals of Biomedical Engineering, 1997)